Learning Motivation and Science Achievement in Third-Grade Students: A Quantitative Study - Riskita, Nurul; Pendit, Sinta Satria Dewi; Surahman, Surahman; Zulnuraini, Zulnuraini; Bulalong, Roberto Rolly (Journal of Innovation and Research in Primary Education, 2025)
This study aims to determine whether there is a relationship between learning motivation and the learning outcomes of third-grade students in the Science subject at SDN Inpres 1 Birobuli. The research employed a descriptive method with a quantitative approach, involving total sampling of all 26 third-grade students. Data were collected through observation, questionnaires, and documentation, and were analyzed using descriptive and inferential statistical techniques. The descriptive analysis showed that 58% of students strongly agreed with the learning motivation statements, while 42% agreed. However, the findings indicated that learning motivation levels did not consistently correspond with students' academic performance. Some students with high motivation achieved moderate learning outcomes, while others with moderate motivation attained high academic results. Inferential analysis revealed that the calculated correlation coefficient (r = 0.072) was lower than the critical value in the r-table, leading to the acceptance of the null hypothesis (Ho) and the rejection of the alternative hypothesis (Ha). It can be concluded that there is no significant relationship between learning motivation and the learning outcomes of third-grade students in the Science subject at SDN Inpres 1 Birobuli. This suggests that learning motivation alone does not directly influence academic performance in this study context.